The Principality of Asturias and the rise of Spanish nationalism in 1808 - Blanco Martín, Carlos Javier (Nómadas. Critical Journal of Social and Juridical Science, 2012)
We try to present some reflections on the attempt to build a sense of retrospective Spanish Nation, based on an old multinational empire, and monarchy Castilian hegemony, taking into account the military-revolutionary events of 1808: Napoleonic invasion and insurrection people. It looks at some of the decisive steps aimed at creating romantic "Nation", more or less coincident in time with the creation myths of other nations or concepts in the European context. The passage of time will demonstrate that this burst bright idea of "Spanish nation" will blur caused by a series of dramatic events.
Keywords: Principality; Asturian General Parliament; Nation; Spanish nationalism; Provincial Charters; multinational State; Asturian Historical Constitution